2022
DOI: 10.3389/fmolb.2022.816102
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ALG3 in Hepatocellular Carcinoma and Its Clinical Implication

Abstract: Background: Recent studies have shown that alpha-1,3-mannosyltransferase (ALG3) promoted tumorigenesis and progression in multiple cancer types. Our study planned to explore the clinical implication and potential function of ALG3 in hepatocellular carcinoma.Materials and Methods: Data from public databases were used to analyze the ALG3 expression and its impact on the clinical significance of patients with HCC. The ALG3 expression was confirmed by qRT-PCR and Western blot. Immunohistochemistry was used to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…There are several glycosyltransferases that also play an important role in cancer biology and are suggested as potential therapeutic targets. ALG3 (Alpha-1,3-Mannosyltransferase) was proved to be significantly upregulated in hepatocellular carcinoma, and its inhibition impeded the tumoral proliferation [44], while it also holds promise as a potential marker for increased sensitivity to radiation therapy, serving as an effective target to reduce radioresistance by modulating the glycosylation of TGFBR2 in breast cancer [45]. In addition, studies have shown that suppression of GALNT6 (pp-GalNAc-T6) decreases the oncofetal fibronectin expression but also effectively reverses the multidrug resistance (MDR) phenotype, as evidenced by heightened sensitivity to various types of anticancer medications [46].…”
Section: Targeting Glycosylationmentioning
confidence: 99%
“…There are several glycosyltransferases that also play an important role in cancer biology and are suggested as potential therapeutic targets. ALG3 (Alpha-1,3-Mannosyltransferase) was proved to be significantly upregulated in hepatocellular carcinoma, and its inhibition impeded the tumoral proliferation [44], while it also holds promise as a potential marker for increased sensitivity to radiation therapy, serving as an effective target to reduce radioresistance by modulating the glycosylation of TGFBR2 in breast cancer [45]. In addition, studies have shown that suppression of GALNT6 (pp-GalNAc-T6) decreases the oncofetal fibronectin expression but also effectively reverses the multidrug resistance (MDR) phenotype, as evidenced by heightened sensitivity to various types of anticancer medications [46].…”
Section: Targeting Glycosylationmentioning
confidence: 99%